Bioassay methods for detection of N-palmitoylbrevetoxin-B2 (BTX-B4) - Bottein, Marie-Yasmine Dechraoui; Fuquay, Jennifer Maucher; Munday, Rex; Selwood, Andrew I.; van Ginkel, Roel; Miles, Christopher O.; Loader, Jared I.; Wilkins, Alistair L.; Ramsdell, John S. (Toxicon (Oxford), 2010)
Brevetoxins (BTXs) are a class of cyclic polyether toxins produced by the dinoflagellate Karenia brevis. These substances are subject to extensive conjugative metabolism in shellfish. BTX-B forms a conjugate with cysteine and is oxidized and reduced to yield BTX-B2, which is further modified by fatty acid addition via cysteine amide linkage to give biologically active brevetoxin metabolites. In this study, we evaluated the commonly used in vitro (ELISA, radioimmunoassay, receptor binding assay and N2A cytotoxicity assay) and in vivo mouse brevetoxin bioassays for the detection of the brevetoxin fatty acid conjugate N-palmitoylBTX-B2, and compared the results to those for dihydroBTX-B and BTX-B2. The receptor binding assay for N-palmitoylBTX-B2 showed comparable sensitivity to that for dihydroBTX-B, and an 11-fold higher sensitivity than for BTX-B2. Although the ELISA showed similarly high sensitivity to dihydroBTX-B and BTX-B2, with EC 50 values of ca. 0.26 ng/ml, it was 23 times less sensitive to N-palmitoylBTX-B2. On the other hand, the N2A cytotoxicity assay was highly sensitive to N-palmitoylBTX-B2, with an EC 50 of 0.15 ng/ml, but was 12- and 40-fold less sensitive to dihydroBTX-B and BTX-B2, respectively. The relative sensitivity of the N2A cytotoxicity assay for each of these metabolites paralleled that of the mouse bioassay (relative LD 50 values 1:20:30 for N-palmitoylBTX-B2:dihydroBTX-B:BTX-B2). We conclude that the most sensitive bioassay for dihydroBTX-B and BTX-B2 is the ELISA, whereas the N2A cytotoxicity assay is most sensitive for N-palmitoylBTX-B2.